Analisis Efektifitas Pemakaian Multiplek Sebagai Bekisting Lantai Dan Balok Di Pakai Secara Berulang Pada Pembangunan Rumah Susun Universitas Tribhuwana Tunggadewi - Rino Rivanto Damsi; Galih Damar Pandulu; Yurnalisdel Yurnalisdel; Diana Ningrum (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
Formwork that is often used in construction projects is multiplex formwork. Multiplex is formwork made of wood and is classified as conventional formwork that is also resistant to moisture. Multiplex is an efficient formwork material because it is easy to produce, economical, and flexible to use, even in constructions with complex designs. The use of efficient and effective construction materials is an important aspect of building design, especially in the context of multi-story building construction. In recent years, the use of multiplex as a construction material for floor and beam formwork has gained greater attention. Multiplex, which is made of bonded layers of wood, has various advantages, such as being lightweight, easy to install, and reusable. The selection of formwork installation methods determines the quality of concrete that can be achieved, because formwork that is too difficult to install or takes too long to reuse will result in suboptimal concrete work. Based on the formwork material shrinkage value on each floor, for example on the first (second) floor with a shrinkage value of 100%-93.45%=6.55% while the shrinkage value on the second floor (third) reaches 100%-88.84%=11.16%, and the effectiveness of repeated formwork use in formwork work is the reuse of formwork on the first floor (first) by 93.45% and on the second floor (second) by 88.84%.